KEPEMIMPINAN CAMAT DALAM MENINGKATKAN DISIPLIN KERJA DI KANTOR CAMAT BARANTI KABUPATEN SIDENRENG RAPPANG - Marwah Ahmad (PRAJA: Jurnal Ilmiah Pemerintahan, 2017)
This research which is discussed as a problem is How the Camat Leadership in Improving Work Discipline at the Baranti Sub-District Office, Sidenreng Rappang Regency, this study aims to find out how the Camat Leadership in Improving Work Discipline at the Baranti Sub-District Office, Sidenreng Rappang Regency and to find out what factors influence The Camat's Leadership in Improving Work Discipline at the Baranti Sub-district Office, Sidenreng Rappang Regency. The population of this study was 44 people, while the sample used a total sample of 44 people. The data collection technique used in this research is to use the techniques of (1) Observation, (2) Interview (3) Questionnaire, and (4) Literature Study. The collected data was then analyzed using frequency and percentage tables. The results of this study indicate that the Camat Leadership indicator with an achievement of 67.5% is in the good category, the work discipline indicator with an achievement of 68.5% is in the good category. leader self 68 %, organizational strength factor 68.33%, situation strength factor 67%, with 67.77% achievement, good category.